P095: Preparing emergency patients and providers study: Clinician and patient satisfaction with communication tool. (May 2019) - Nunn, J.; Chiasson, D.; Cassidy, C.; MacPhee, S.; Rose-Davis, B.; Curran, J.
Abstract : Introduction : Effective communication to develop a shared understanding of patient/caregiver (P/C) expectations is critical during emergency department (ED) encounters. However, there is limited research examining the use of communication tools of P/C expectations to improve communication in the ED. The objective of this study was to examine satisfaction with a patient expectations questionnaire, known as the PrEPP tool, and its impact on communication and management of patients in the ED.Methods : The PrEPP tool collected P/C expectations over 3 phases of the study. In phase1, the PrEPP tool was distributed to all P/Cs (CTAS score of 2 to 5) in four EDs in Nova Scotia. In phase 2 the PrEPP tool was refined to a 5-item questionnaire. In phase 3 the PrEPP tool was re-implemented over a six-month period. Follow-up surveys were distributed to P/Cs via email (phase 1, 3) and HCPs on iPads in the ED (phase 3) to determine the impact of the tool on communication and management of patients. Entries were compiled on a REDCap database and descriptive statistics were used to analyze responses related to satisfaction.The PrEPP tool collected P/C expectations over 3 phases of the study. In phase1, the PrEPP tool was distributed to all P/Cs (CTAS score of 2 to 5) in four EDs in Nova Scotia. In phase 2 the PrEPP tool was refined to a 5-item questionnaire. In phase 3 the PrEPP tool was re-implemented over a six-month period. Follow-up surveys were distributed to P/Cs via email (phase 1, 3) and HCPs on iPads in the ED (phase 3) to determine the impact of the tool on communication and management of patients. Entries were compiled on a REDCap database and descriptive statistics were used to analyze responses related to satisfaction.Results : In Phase 1, 11418 PrEPP tools and 147 surveys (29% response rate) were collected from January-June 2016. The majority of P/Cs found the PrEPP questionnaire easy to complete (95.9%) and felt HCPs met their expectations (87.1%). In Phase 3, 951 P/C (31.1% response rate) and 128 HCP surveys were collected. Of P/C respondents 45.9% felt PrEPP helped to communicate expectations, while 49.7% said that they would like to use it on future ED visits. The majority of P/C respondents (75.4%) indicated their expectations were met during their visit to the ED. Of those whose expectations were not met, 69% felt their expectations were not discussed. The majority of HCP respondents (90.4%) indicated they used the PrEPP tool at least sometimes. Also, 78.4% said it influenced patient communication and 42% indicated the tool influenced management of patients at least sometimes.Conclusion : Obtaining expectations early in the patient encounter may provide opportunities for improved communication in the ED. P/Cs found the PrEPP tool easy to use to communicate their expectations and HCPs felt it influenced communication and management of patients in the ED. Further qualitative thematic analysis is needed to explore how the PrEPP tool impacted ED visits.